Respuesta :

Answer:

(2c^2+3)(2c-1)(2c+1)

Step-by-step explanation:

8c^4+10c^2-3

8c^4+12c^2-2c^2-3

4c^2(2c^2+3)-(2c^2+3)

(2c^2+3)(4c^2-1)

(2c^2+3)(2c-1)(2c+1)

Given polynomial in the question,

8c⁴ + 10c² - 3

Coefficient of c⁴ = 8

Coefficient of c² = 10

Constant term = -3

Steps to factorize the given polynomial,

  • Multiply the coefficients of c⁴ and the constant term.
  • Split the result of multiplication into two numbers such that the addition of two numbers equals to the coefficient of c².

Multiplication of 8 and (-3) = 8(-3) = -24

Split (-24) into two numbers such that sum of these numbers is equal to coefficient of c².

(-24) = (12)(-2)

Addition of 12 and -2 = 12 - 2 = 10

Therefore, 8c⁴ + 10c² - 3 = 8c⁴ + 12c² - 2c² - 3

                                         = 4c²(2c² + 3) - 1(2c² + 3)

                                         = (4c²- 1)(2c² + 3)

                                         = (2c - 1)(2c + 1)(2c² + 3) [a² - b² = (a - b)(a + b)]

Therefore, factored form of the given polynomial is (2c - 1)(2c + 1)(2c² + 3).

Learn more,

https://brainly.com/question/16078564